Strategi Komunikasi Zakat Indonesia dalam Optimalisasi Layanan Ziswaf untuk Atasi Kemiskinan dan Pengangguran - Yuda Prasetia Darma; Rahmanita Ginting; Muhammad Thariq (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article or paper aims to analyze the communication strategy of the Indonesian Zakat Initiative as a philanthropic movement in optimizing ZISWAF donation services to alleviate poverty and unemployment in the city of Medan, as well as its supporting and inhibiting factors. This study uses Harold Lasswell's communication theory and a qualitative approach with a descriptive method. The subjects of the study are the Head of the North Sumatra Indonesia Zakat Initiative Program, the Person in Charge of the Program, and the Person in Charge of ZISWAF Services. The object of the research is the communication strategy of the Indonesian Zakat Initiative in optimizing ZISWAF donation services. Data collection techniques include interviews, observations, documentation, and data analysis through data reduction, data presentation, and conclusions drawn. This study shows that the Indonesian Zakat Initiative's communication strategy in ZISWAF services effectively reduces poverty and unemployment. The strategy involves social media, community campaigns, and institutional partnerships, as well as empowerment programs such as skills training. Supporting factors include the communicator's credibility, message relevance, and two-way feedback, while barriers include limited understanding, inappropriate media, low communicative understanding, cultural differences, and negative experiences.